Changes in apparent diffusion coefficient and T2 relaxation during radiotherapy for prostate cancer. Issue 4 (23rd October 2012) - Foltz, Warren D.; Wu, Andy; Chung, Peter; Catton, Charles; Bayley, Andrew; Milosevic, Michael; Bristow, Robert; Warde, Padraig; Simeonov, Anna; Jaffray, David A.; Haider, Masoom A.; Ménard, Cynthia
Abstract Purpose: To evaluate regional and temporal changes in apparent diffusion coefficient (ADC) and T2 relaxation during radiation therapy (RT) in patients with low and intermediate risk localized prostate cancer. Materials and Methods: Seventeen patients enrolled on a prospective clinical trial where MRI was acquired every 2 weeks throughout eight weeks of image‐guided prostate IMRT (78 Gy/39 fractions). ADC and T2 quantification used entire prostate, central gland, benign peripheral zone, and tumor‐dense regions‐of‐interest, and mean values were evaluated for common response trends. Results: Overall, the RT responses were greater than volunteer measurement repeatability, and week 6 appeared to be an optimum time‐point for early detection. RT effects on the entire prostate were best detected using ADC (5–7% by week 2, P < 0.0125), effects on peripheral zone were best detected using T2 (19% reduction at week 6; P = 0.004) and effects on tumors were best detected using ADC (14% elevation at week 6; P = 0.004). Conclusion: ADC and T2 may be candidate biomarkers of early response to RT warranting further investigation against clinical outcomes. J. Magn. Reson. Imaging 2013;37:909–916. © 2012 Wiley Periodicals, Inc.